(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article deals with public-private partnerships as advanced, proven international practice form of cooperation between the state and private business. The necessity of intensification of public-private partnership in Ukraine and proposes mechanisms for implementing basic models of public-private partnership for economic development.The article deals with public-private partnerships as advanced, proven international practice form of cooperation between the state and private business. The necessity of intensification of public-private partnership in Ukraine and proposes mechanisms for implementing basic models of public-private partnership for economic development.